Evaluation of Diagnostic Role of Alkaline Phosphatase in the Patients of Cerebral Stroke - Madiha Shah, Razia Bano, Kashif Ali, Hafiz Abdul Rauf, Ishaque Bhatti, Ali Raza Memon, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The cerebral stroke is one of the most common disorders in South Asia. The Pakistani adult population suffered from cerebral strokes in more than 10% of cases. The TNAP isoform of Alkaline Phosphatase is also found in the brain. It is possible to diagnose cerebral stroke patients based on their serum ALP level. In this study, the objective is to evaluate the level of ALP in patients suffering from cerebral strokes. Methodology: This cross-sectional study was conducted at the Department of Medicine at the LUMHS Jamshoro. A total of 55 patients (26 males & 29 females) with cerebral stroke between the ages of 40-70 years were selected according to the inclusion & exclusion criteria between the ages of 40-70 years. By using the AMP (2-amino, 2-methyl, 1 propanol) method, we were able to estimate the serum level of ALP. Results: In 29.1% of the patients, the mean serum ALP level was 85.13 ± 10.93 U/L, while in 70.9% of the patients, the mean serum ALP level was 231 .42 ± 5.76 U/L. As a result of this study, it can be concluded that approximately 70% of cerebral stroke patients had elevated levels of serum ALP levels, which can be used as a diagnostic tool for cerebral stroke patients. Conclusion: Cerebral stroke patients had elevated serum ALP levels, which are a cheap and easily quantifiable biomarker.